Nordic Peoples Survey - Holzinger, Katharina; Kupisch, Tanja; Bergmann, Fabian; Lloyd-Smith, Anika; Schmid, Sven-Patrick; Yasar, Rusen (Harvard Dataverse, 2023)
The dataset presents responses to 'Nordic Peoples Survey', conducted in the northern regions of Norway and Sweden between April and September 2021. The survey is part of the interdisciplinary research project “'Ethnic Policies' – Remedy for Between-Group Inequalities?", consisting of political scientists and linguists from the Cluster of Excellence: Politics of Inequality, University of Konstanz, Germany. The project was funded by the Deutsche Forschungsgemeinschaft (DFG – German Research Foundation) under Germany’s Excellence Strategy – EXC-2035/1 – 390681379. As of August 2023, the files are limited to the replication files for the article "Experience of Discrimination in Egalitarian Societies: The Sámi and Majority Populations in Sweden and Norway". As soon as the full dataset is ready for public access, the files will be updated.